WANPRESTASI DALAM KONTRAK KERJA KONSTRUKSI YANG MENGAKIBATKAN KERUGIAN NEGARA BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2017 TENTANG JASA KONSTRUKSI - Kamaluddin Kamaluddin (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT The implementation of construction work services is inseparable from the contract. The construction work contract governs the rights and obligations of service providers and service users. If an obligation is not carried out by one party, the party is said to have defaulted and is detrimental to the other party. For these losses, the party causing the loss must provide compensation, as stipulated in Law Number 2 of 2017.This type of research used in this study is normative juridical, with descriptive-analytical research specifications. The legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials, which are obtained through literature study, then analyzed qualitatively.The results of this study are : (1) defaults in construction work contracts that result in state losses based on Law Number 2 of 2017 concerning Construction Services can occur due to the form of contract performance or make achievements that are not in accordance with the contract, late in carrying out performance that is not appropriate with the coverage period, and the service provider does not carry out its obligations at all. Violations that often occur are late completion of work by the contractor; (2) The legal consequences of defaults in construction work contracts that result in state losses based on Law Number 2 of 2017 concerning Construction Services are that the party causing the loss must pay compensation to the injured party. The construction dispute can be resolved with the basic principle of deliberation to reach an agreement, but if no agreement is reached, then it can go through the stages of dispute resolution efforts through mediation, conciliation, or arbitration. Keywords : Construction Work Contracts, Defaults, State Losses